Factors Affecting the Completion of Physical Education Study Program Students' Theses - Muhammad Akbar Syafruddin; Agus Sutriawan (Journal Physical Health Recreation (JPHR), 2025)
This study uses a descriptive method with a quantitative approach. This method was chosen to systematically and accurately describe the factors that influence the completion of thesis of Physical Education and Sports students, both inhibiting and driving factors. This study aims to determine the percentage of influential factors based on data obtained from interviews with 37 students. The sampling technique was carried out by simple random sampling. The data obtained from the interview results were then processed in the form of a percentage to determine the dominant factors that influence students. Based on the results of the study, it is known that the largest supporting factor for students in completing their thesis is family support of 37.8%, then the support factor of the supervisor is 27%, deadline pressure is 16.2%, personal motivation is 13.5%, and friend support is 5.4%. While the inhibiting factors are lack of motivation of 32.4%, then the difficulty factor in data collection is 24.3%, ineffective guidance is 18.9%, time constraints are 13.5%, lack of references or literature is 8.1%, and personal problems are 2.7%.